Irrational beliefs and teaching assertiveness with violence in schools - Orellana Manrique, Oswaldo (2013)
The goal of search indicators cognitive, affective and social good teaching practices, research motivate this descriptive and correlational in nature. The three selected variables have been studied with instruments that assess irrational beliefs, assertiveness and the judgment criterion was the school violence. The first two formats that validity and reliability enjoyed by the authors and countless investigations, and the third a specific construction for this research, the same that have been subjected to analysis of statistical consistency, and the content and conceptual extension theoretical systems that sustain.